2023
DOI: 10.3389/fmolb.2023.1146606
|View full text |Cite
|
Sign up to set email alerts
|

Automatic interictal epileptiform discharge (IED) detection based on convolutional neural network (CNN)

Abstract: Clinical diagnosis of epilepsy significantly relies on identifying interictal epileptiform discharge (IED) in electroencephalogram (EEG). IED is generally interpreted manually, and the related process is very time-consuming. Meanwhile, the process is expert-biased, which can easily lead to missed diagnosis and misdiagnosis. In recent years, with the development of deep learning, related algorithms have been used in automatic EEG analysis, but there are still few attempts in IED detection. This study uses the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Including studies using either or both of these measures, twenty-two relevant studies were found spanning the years 2016–2023. The median ACC is 0.90 (min: 0.71; max: 1.00) and the median AUC is 0.94 (0.76, 1.00) (Abou Jaoude et al, 2020;Antonaides et al, 2017; Cheng et al, 2022; Chung et al, 2023; Faghihpirayesh et al, 2021; Fürbass et al, 2020; Geng et al, 2021; Jeon et al, 2022; Jiang et al, 2023; Johansen et al, 2016; Kural et al, 2022; McDougall et al, 2023; Medvedev et al, 2019; Nejedly et al, 2023; Nhu et al, 2023; Thangavel et al, 2021; Thomas et al, 2020; Thomas et al, 2021; Tjepkema-Cloostermans et al, 2018; Wang et al, 2023; Wei et al, 2021; Zhang et al, 2023). In these studies, there is a large variation in data sizes, in the methods to calculate ACC (e.g., some used balanced ACC) and AUC (e.g., ROC vs. precision and recall), making comparisons difficult.…”
Section: Introductionmentioning
confidence: 99%
“…Including studies using either or both of these measures, twenty-two relevant studies were found spanning the years 2016–2023. The median ACC is 0.90 (min: 0.71; max: 1.00) and the median AUC is 0.94 (0.76, 1.00) (Abou Jaoude et al, 2020;Antonaides et al, 2017; Cheng et al, 2022; Chung et al, 2023; Faghihpirayesh et al, 2021; Fürbass et al, 2020; Geng et al, 2021; Jeon et al, 2022; Jiang et al, 2023; Johansen et al, 2016; Kural et al, 2022; McDougall et al, 2023; Medvedev et al, 2019; Nejedly et al, 2023; Nhu et al, 2023; Thangavel et al, 2021; Thomas et al, 2020; Thomas et al, 2021; Tjepkema-Cloostermans et al, 2018; Wang et al, 2023; Wei et al, 2021; Zhang et al, 2023). In these studies, there is a large variation in data sizes, in the methods to calculate ACC (e.g., some used balanced ACC) and AUC (e.g., ROC vs. precision and recall), making comparisons difficult.…”
Section: Introductionmentioning
confidence: 99%